2023
DOI: 10.3233/cbm-210538
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of TNFRSF4 impacts immune cell infiltration and gene mutation in hepatocellular carcinoma

Abstract: BACKGROUND: Hepatocellular carcinoma (HCC) is a highly heterogeneous disease, which makes prognostic prediction challenging.We aimed to investigate association of TNFRSF4 expression with the immune infiltration and gene mutation in HCC. METHODS: In this study, the expression profiles and corresponding clinical data of HCC patients were downloaded from the Cancer Genome Atlas (TCGA) database. Kaplan-Meier and Cox regression were used to evaluate the clinical value of TNFRSF4. ESTIMATE and CIBERSORT algorithms w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…Our results demonstrated that elevated TNFRSF4 expression was associated with a significant reduction in OS in the HCC population. This finding supports previous research that has indicated TNFRSF4 expression as a prognostic marker in various cancers, including HCC [ 28 , 29 ]. The association between TNFRSF4 expression and OS remained significant even after adjusting for multiple clinical factors, indicating that TNFRSF4 expression can independently predict patient outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…Our results demonstrated that elevated TNFRSF4 expression was associated with a significant reduction in OS in the HCC population. This finding supports previous research that has indicated TNFRSF4 expression as a prognostic marker in various cancers, including HCC [ 28 , 29 ]. The association between TNFRSF4 expression and OS remained significant even after adjusting for multiple clinical factors, indicating that TNFRSF4 expression can independently predict patient outcomes.…”
Section: Discussionsupporting
confidence: 92%
“…40 TNFRSF4, known as OX40 or CD134 is expressed primarily on activated T cells and can activate the NF-kappa-B pathway by mediating TRAF2, TRAF5, PI3K/PKB, and NFAT pathways. 41 The most important function of TNFRSF4 is to enhance cellular division, proliferation, survival, and cytokine production of T cells by activating the pathways described above, with a potential role in immunotherapy. The PI3 gene encodes an elastase-specific inhibitor peptide against Gram-positive and Gram-negative bacteria, and fungal pathogens, and its expression is upregulated by both bacterial lipopolysaccharides and cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CCDC85B is regulated in a p53‐dependent manner (p‐53 has anti‐oncogenic actions blocking β‐catenin‐dependent gene expression in the nucleus) 40 . TNFRSF4 , known as OX40 or CD134 is expressed primarily on activated T cells and can activate the NF‐kappa‐B pathway by mediating TRAF2, TRAF5, PI3K/PKB, and NFAT pathways 41 . The most important function of TNFRSF4 is to enhance cellular division, proliferation, survival, and cytokine production of T cells by activating the pathways described above, with a potential role in immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…TNFRSF4 is one of the major members of the TNF receptor-family member 4 (TN-FRSF4) and is mainly inducibly expressed in activated CD4+ and CD8+ cells [ 47 ]. TNFRSF4, combined with its ligand, can promote the proliferation of T cells, prevent the development of immune tolerance [ 48 ], and play an important role in the immune environment [ 49 ]. In our study, we found that TNFRSF4 was lost in WECP populations.…”
Section: Discussionmentioning
confidence: 99%